2021
DOI: 10.1001/jamanetworkopen.2021.20165
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hepatotoxicity Associated With New BCR-ABL Tyrosine Kinase Inhibitors vs Imatinib Among Patients With Chronic Myeloid Leukemia

Abstract: IMPORTANCE Although BCR-ABL fusion oncoprotein tyrosine kinase inhibitors (BCR-ABL TKIs) can substantially improve the survival rate of chronic myeloid leukemia (CML), they are clinically accompanied by severe hepatotoxicity. OBJECTIVE To compare the relative risk (RR) of hepatotoxicity of new-generation BCR-ABL TKIs with that of imatinib, and to provide an overall assessment of the clinical benefit. DATA SOURCES PubMed, Embase, Cochrane library databases, and ClinicalTrials.gov were searched for clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
(77 reference statements)
1
12
0
Order By: Relevance
“…29 A previous study reported a lowgrade elevation in serum ALT and/or AST in 25% to 30% and a high-grade elevation in approximately 2% of patients treated with TKIs. 32 Also, Khelifa et al, (2022) reported that elevated hepatic enzymes (grade 3 or 4) were seen in 10% to 15% of patients treated with Nilotinib but rarely progress to hepatitis. 33 The systematic review and meta-analysis by Wang et al, (20121) which included 9 trials involving 3475 patients showed that patients received new-generation TKIs were more likely to experience all grades of ALT and AST elevation compared with those received Imatinib (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 A previous study reported a lowgrade elevation in serum ALT and/or AST in 25% to 30% and a high-grade elevation in approximately 2% of patients treated with TKIs. 32 Also, Khelifa et al, (2022) reported that elevated hepatic enzymes (grade 3 or 4) were seen in 10% to 15% of patients treated with Nilotinib but rarely progress to hepatitis. 33 The systematic review and meta-analysis by Wang et al, (20121) which included 9 trials involving 3475 patients showed that patients received new-generation TKIs were more likely to experience all grades of ALT and AST elevation compared with those received Imatinib (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…32 Also, Khelifa et al, (2022) reported that elevated hepatic enzymes (grade 3 or 4) were seen in 10% to 15% of patients treated with Nilotinib but rarely progress to hepatitis. 33 The systematic review and meta-analysis by Wang et al, (20121) which included 9 trials involving 3475 patients showed that patients received new-generation TKIs were more likely to experience all grades of ALT and AST elevation compared with those received Imatinib (p<0.001). New-generation TKIs drugs were associated with a significantly higher rate of MMR at 1 year compared with Imatinib (p< 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Dasatinib-induced hyperbilirubinemia is rare in patients with CML-CP or accelerated phase disease (1%); nevertheless, it is more common in those with blast phase disease (4–5%) ( 58 ). A recent meta-analysis showed that bosutinib, nilotinib, or ponatinib were associated with a higher risk of hepatotoxicity than imatinib; however, dasatinib was not linked to a significantly increased risk ( 59 ). The mechanism of dasatinib-related hepatotoxicity remains unclear.…”
Section: Clinical Characteristic Of Dasatinib Related Aes In Patients...mentioning
confidence: 99%
“…BCR::ABL1‐dependent activation of Src kinase also contributes to the pathogenesis of CML 3 . BCR::ABL1 tyrosine kinase inhibitors (TKIs) such as imatinib, nilotinib and dasatinib are currently the first‐line agents for the treatment of CML 4 . Compared to conventional interferon therapy, these inhibitors have markedly improved the 5‐year survival rate of chronic phase CML patients to more than 90% 5 .…”
Section: Introductionmentioning
confidence: 99%